An exploration of spousal caregivers' well-being after the death of their partners who were older cancer patients – A phenomenological approach. (August 2020) - Van Hout, E.; Peters, S.; Jansen, L.; Rober, P.; van den Akker, M.
Abstract: Purpose: The aim of this study was to gain more insight into the psychosocial well-being of the recently bereaved spouses who took care of their partners with cancer. Method: A qualitative study was developed, taking a phenomenological approach. Eleven former caregivers and spouses of patients who died of cancer at, or after, the age of 64, participated in individual in-depth interviews. Only caregivers who were bereaved for a minimum of three months and maximum of one year were interviewed. The analysis of the data was based on the Qualitative Analysis Guide of Leuven. Results: The first moments of bereavement included feelings of disbelief, regret and relief. A feeling of being overwhelmed during this time was reported by some, others sought distraction from their grief. Loneliness, emotional fluctuations and a sense of appreciation for the support of loved ones were dominant themes. Also, gratitude and the importance of consolation played a role in the participants' well-being. When participants addressed the matter of moving forward in life, most explained how they wanted to keep the memories of their partner alive while rebuilding their lives. Conclusions: The present study offers insight into the experiences of the bereaved spousal caregiver and highlights the need of social support during the bereavement period. All participants expressed loss-oriented and restoration-oriented coping strategies. Also, loneliness is considered a dominant feeling throughout the bereavement period. Social contact can ease these feelings of loneliness through providing either distraction or possibilities to share the burden. This paper emphasized the importance of improving access to healthcare professionals during bereavement. Highlights: Prominent feelings and needs of bereaved caregivers were highlighted. Loneliness is considered to be a dominant feeling after bereavement of the patient. Social contact can reduce loneliness by providing distraction and sharing the burden. Facilitating access to support from professionals during bereavement is essential.